Digital transformation of the Russian media business in the face of uncertainty - A. M. Druzhinin (Цифровая социология)
The article is of a theoretical nature, and all reasoning is based on qualitative research methods on the controversial issues of the digital transformation of the domestic media business. The conditions of uncertainty, within which the decision-makers in this socio-economic sphere of activity act today, are the key feature of digital transformation process. The reasons, impeding the implementation of innovations in the media industry, have been analysed. The factors, under which the organisation avoids risky experiments in management of media production, have been highlighted.It has been concluded that modern media players have to adapt to changing environmental conditions faster than their competitors, and the adaptation process is the basis for developing a competitive advantage in the market. Platforms, technologies and algorithms are implemented into media production, in no small part, in the context of an understanding of the infosphere and technosphere processes within the framework of actor-network theory. They perform work on an equal level with the subjects. This process introduces significant amendments to the structures, business processes, and financial models of the media industry. Finding ways to make the best changes is a key dilemma for media organisations. On the one hand, it is beneficial for them to exploit existing capabilities, resources, and competencies. On the other hand, renewal and adaptation are dictated by such organisations by the external environment, while simultaneously increasing costs and risks.